Phage display demonstrates durable differences in serological profile by route of inoculation in primary infections of non-human primates with Dengue Virus 1 - Jayant V. Rajan (Nature Portfolio, 2021)
Abstract Natural dengue virus (DENV) infections occur by mosquito bite but how the inoculation route affects the humoral immune response is unknown. We serologically profiled 20 non-human primates (NHP) from a prior study of DENV1 infection where animals were inoculated by mosquito (N = 10) or subcutaneous injection (N = 10). Using a comprehensive, densely tiled and highly redundant pan-flavivirus programmable phage library containing 91,562 overlapping 62 amino acid peptides, we produced a high-resolution map of linear peptide sequences enriched during DENV seroconversion. Profiles in mosquito-inoculated and subcutaneously-inoculated animals were similar up to 90 days after primary infection, but diverged at 1 year with differences in sero-reactivity in the Envelope (E; residues 215–406; p < 0.08), and Nonstructural-3 (NS3; residues 549–615; p < 0.05) proteins in mosquito-inoculated versus subcutaneously-inoculated animals. Within the E protein, residues 339–384 in domain III accounted for > 99% of the observed sero-reactivity difference. Antibody breadth did not vary by mode of inoculation. The differential reactivity to E domain III seen by phage display validated orthogonally by ELISA, but did not correlate with late neutralization titers. Serological profiling of humoral immune responses to DENV infection in NHP by programmable phage display demonstrated durable differences in sero-reactivity by route of inoculation.